2018
DOI: 10.1080/02678292.2018.1492035
|View full text |Cite
|
Sign up to set email alerts
|

Elastocaloric effect in liquid crystal elastomers from molecular simulations

Abstract: Large-scale molecular simulations of the elastocaloric effect in swollen monodomain main-chain liquid crystal elastomers are performed, following the so-called indirect approach where the magnitude of the effect is extracted from the system's equation of state connecting stress, strain, and temperature. The presented isostress off-lattice Monte Carlo simulations are based on the soft-core Gay-Berne potential and predict an elastocaloric temperature increase that exceeds ∼ 10 K upon applying an external enginee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Our molecular simulations largely follow the methodology presented in Ref. [34]. In the simulation, mesogenic units are represented by uniaxial ellipsoidal particles interacting via the soft-core Gay-Berne (GB) potential [35,36].…”
Section: Sample Preparation Procedures and Experimentalmentioning
confidence: 99%
See 2 more Smart Citations
“…Our molecular simulations largely follow the methodology presented in Ref. [34]. In the simulation, mesogenic units are represented by uniaxial ellipsoidal particles interacting via the soft-core Gay-Berne (GB) potential [35,36].…”
Section: Sample Preparation Procedures and Experimentalmentioning
confidence: 99%
“…The less densely crosslinked sample presents a slightly lower nematicisotropic transition temperature and a steeper temperature dependence of near the nematicisotropic phase transition in comparison with its more densely crosslinked counterpart. Now, the elastocaloric response is dominated by the absolute value of the derivative ( ) [31][32][33][34], i.e., higher slopes result in a more pronounced response. In addition, a steeper slope also indicates that the transition moves toward the first order regime below the critical point in agreement with early experiments [31,32].…”
Section: A Monte Carlo Simulations and The Thermomechanical Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Experimental efforts have so far demonstrated elastocaloric temperature changes of only ∆T ∼ 1 K. 14,22 Lavrič et al observed ∆T = 1 K at a strain of ε = 90% and detailed that this ∆T was observed across a range of crosslink density. 22 Skačej has reported molecular simulations that suggest the elastocaloric effect in mainchain LCEs could yield a ∆T > 10 K. 23 However, the simulations underestimate the specific heat of liquid crystal-containing systems, which likely leads to an overestimate of the elastocaloric temperature change. LC systems also have been explored as electrocaloric materials, notably harnessing a smectic-to-isotropic transition to achieve a ∆T + of up to 5.2 to 6.5 K. 14,24 Our group has recently quantified the transition from disorder (order parameter Q ≈ 0) to appreciable order (Q ≈ 0.4, i.e., the nematic phase) in a liquid crystal-containing elastomeric network upon application of uniaxial strain.…”
Section: Introductionmentioning
confidence: 99%
“…This process is macroscopically manifested as the size shrinkage of LCEs in the orientation direction. [40,41] Therefore, the orientation degree of LCEs affects the maximum deformation actuated by the external stimuli to a large extent, whereas the orientation direction of LCEs determines their macroscopic deformation direction. The programmability of the mesogen orientation lays a foundation for achieving versatile deformation actuations of LCEs.…”
mentioning
confidence: 99%